PENERAPAN INTERVENSI BERDASARKAN EVIDENCE BASED NURSING: NAFAS DALAM DAN GENGGAM JARI PADA NYERI POST APPENDIDTOMY: APPLICATION OF INTERVENTION EVIDENCE BASED NURSING: DEEP BREATHING AND FINGER HOLD IN PAIN IN POST APPENDECTOMY - Santoso, Shelfi Dwi Retnani Putri; Agustin, Veranica Dwi; Nurjanah, Suci (WELL BEING, 2022)
Appendectomy is an operation to remove the appendix. The risks or side effects of an appendectomy are pain resulting from a surgical wound in the abdomen. The purpose of this study was to describe nursing care for post-appendectomy clients by application interventions based on evidence based nursing: deep breathing and finger holding. The research method used is descriptive case study research. Collecting data using interview and observation methods. This study used two clients with post appendectomy, given nursing care and deep breathing therapy and finger holding for 3 days. The results of the study found acute pain problems in client 1 and client 2, and after the care was carried out the results of the nursing evaluation for client 1 and client 2 showed that all problems were partially resolved on the third day. The conclusion of this study is that these two interventions can be used as recommendations in managing pain in post-appendectomy patients.